Different AMPA receptor subtypes mediate the distinct kinetic components of a biphasic EPSC in hippocampal interneurons - Stincic, Todd L.; Frerking, Matthew E. (Frontiers in Synaptic Neuroscience, 2015)
CA1 hippocampal interneurons at the border between stratum radiatum and stratum lacunosum-moleculare have AMPA receptor (AMPAR)-mediated excitatory postsynaptic currents (EPSCs) that consist of two distinct phases: a typical fast component (FC), and a highly unusual slow component (SC) that persists for hundreds of milliseconds. To determine whether these kinetically distinct components of the EPSC are mediated by distinct AMPAR subpopulations, we examined the relative contributions of GluA2-containing and –lacking AMPARs to the SC. GluA2-containing AMPARs mediated the majority of the FC whereas GluA2-lacking AMPARs preferentially generated the SC. When glutamate uptake through the glial glutamate transporter EAAT1 was inhibited, spill over-mediated AMPAR activation recruited an even slower third kinetic component that persisted for several seconds; however, this spillover-mediated current was mediated predominantly by GluA2-containing AMPARs and therefore was clearly distinct from the SC when uptake is intact. Thus, different AMPAR subpopulations that vary in GluA2 content mediate the distinct components of the AMPAR EPSC. The SC is developmentally downregulated in mice, declining after the second postnatal week. This downregulation affects both GluA2-containing and GluA2-lacking AMPARs mediating the SC, and is not accompanied by developmental changes in the GluA2 content of AMPARs underlying the FC. Thus, the downregulation of the SC appears to be independent of synaptic GluA2 expression, suggesting the involvement of another AMPAR subunit or an auxiliary protein. Our results therefore identify GluA2-dependent and GluA2-independent determinants of the SC: GluA2-lacking AMPARs preferentially contribute to the SC, while the developmental downregulation of the SC is independent of GluA2 content.